Kiprah Perempuan Pemimpin Di Pemerintahan Daerah - Evi Lorita; Anis Endang; Bayu Risdiyanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to explain the role of women leaders in local government, in this case Dusun 001, in carrying out leadership roles and trying to advance the welfare of the community. The research method used is descriptive-qualitative, and research data were collected through interviews, observation, and literature study. There were three informants in the study: Yustina Sumini (head of Dusun 001), Sumadi (community leader), and Aseni (head of the women farmer group). From the results of the study, it was found that female leaders can make a lot of contributions and are more effective at mobilizing citizens, especially women. Yustina Sumini's leadership belongs to the category of transforming entrepreneurial leadership type. This can be found in the elements led by Yustina Sumini in mobilizing and inviting mothers to engage in the creative economy to improve family welfare.